Similarity judgements: the comparison of normative predictions and subjective evaluations – A study of the ratio model of similarity in social context - Jabłońska, Magdalena Zyta; Falkowski, Andrzej; Mackiewicz, Robert (Frontiers in Psychology, 2024)
Introduction This study examines the consistency between subjective similarity evaluations and the theoretical predictions derived from Tversky’s ratio model of similarity, alongside the impact of additional positive and negative features on perceived similarity to ideal and bad politicians. Methods Using a sample of 120 participants, we assessed the similarity of eight candidate profiles to an ideal and bad politician, varying in positive and negative features. Participants’ subjective evaluations were compared with theoretical predictions derived from Tversky’s ratio model. The analysis focused on how candidate and referent valence influenced observed versus theoretical similarity. Results Subjective similarity judgments deviated systematically from theoretical predictions, especially for positively featured candidates, indicating a negativity effect. Additional positive features decreased the perceived similarity of favorable candidates to an ideal politician, while additional negative features did not significantly affect similarity judgments of unfavorable candidates. Discussion Our findings underscore a significant disparity between subjective and objective similarity judgments, notably for favorable candidates. While the ratio model performs well for unfavorable candidates, its applicability diminishes for favorable ones, emphasizing the role of feature valence in decision-making. Further research on feature valence is crucial for a comprehensive understanding across contexts.